Design and Development of Test Rig for Conversion of Pure Bio Oil Onto Biodiesel for Internal Combustion Engine Using Acidic (Esterification) Method and Alkaline (Trans-Esterification) Method - Muhammad Shahrin, Sabri; M. M. A., Rahman; F. T., Suhaimi; A. S., Ngah; A., Aseli; Muhammad Fazrul Qazwan, Mohd Zaki (2015)
This project is to design and development of test rig for conversion of pure bio oil into biodiesel for internal combustion engine using acidic method and alkaline method. When compared toseveral other alternative fuels available, Biodiesel comes out way ahead. Most alternative fuels require changes to a vehicle to be used[1]. Natural Gas & Propane require special tanks to be installed and changes to the fuel injection system must be made as well[2]. Lately, biodiesel produce by the trans-esterification of vegetable oils or animal fats with simple alcohols and catalyst becomes more popular[3]. Biodiesel is clean burning diesel alternative and has many attractive features including renewability, biodegradability, non-toxicity and low emission[4]. It observes that the base catalysts are more effective than acid catalysts. Biodiesel is different.[5]. Unlike other alternative fuels, Biodiesel can be used in most any diesel vehicle unmodified[6]. Biodiesel is a notable alternative to the widely used petroleum-derived diesel fuel since it can be generated by domestic and non-domestic sources such as soybeans, coconuts, waste frying oil, etc. and thus these reduces dependence on diminishing petroleum fuel from foreign sources[7]. When Biodiesel is used in place of petro-diesel, it reduces the amount of crude oil used up[8]. This means that it helps to reduce dependence on a limited resource and increases the use of renewable resources[9].